2021
DOI: 10.5194/bg-2021-117
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mercury accumulation in leaves of different plant types – the significance of tissue age and specific leaf area

Abstract: Abstract. Mercury, Hg, is one of the most problematic metals from an environmental perspective. To assess the problems caused by Hg in the environment it is crucial to understand the processes of Hg biogeochemistry, but the exchange of Hg between the atmosphere and vegetation is not sufficiently well characterised. We explored the mercury concentration, [Hg], in foliage from a diverse set of plant types, locations and sampling periods to study whether there is a continuous accumulation of Hg in leaves/needles … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
(59 reference statements)
4
4
0
Order By: Relevance
“…We therefore suggest that differences in daily foliar Hg uptake rates between the sampling years 2015 and 2017 are negligible. In agreement with previous studies (Ollerova et al, 2010;Hutnik et al, 2014;Navrátil et al, 2019;Wohlgemuth et al, 2020;Pleijel et al, 2021), we found a clear trend of Hg concentrations in differently aged needles with older needles exhibiting higher Hg concentrations (Fig. 7), demonstrating that Hg accumulation continues in older needles.…”
Section: Foliar Hg Uptake and Geographic And Tree-specific Parameterssupporting
confidence: 93%
See 1 more Smart Citation
“…We therefore suggest that differences in daily foliar Hg uptake rates between the sampling years 2015 and 2017 are negligible. In agreement with previous studies (Ollerova et al, 2010;Hutnik et al, 2014;Navrátil et al, 2019;Wohlgemuth et al, 2020;Pleijel et al, 2021), we found a clear trend of Hg concentrations in differently aged needles with older needles exhibiting higher Hg concentrations (Fig. 7), demonstrating that Hg accumulation continues in older needles.…”
Section: Foliar Hg Uptake and Geographic And Tree-specific Parameterssupporting
confidence: 93%
“…Average foliar Hg concentrations (mean ± sd) differed between tree species groups (see Table S1 for definition of tree species groups). Ash leaves exhibited highest Hg concentrations (32.2 ± 5.7 ng Hg g -1 d.w.; n = 10), followed by beech leaves (25.5 ± Increasing foliar Hg concentrations with progressing sampling date are in line with previous observations demonstrating that at individual sites Hg concentrations increased linearly over the growing season (Rea et al, 2002;Laacouri et al, 2013;Wohlgemuth et al, 2020;Pleijel et al, 2021). To make Hg levels in foliage sampled at different times comparable, we calculated daily foliar Hg uptake rates by normalizing foliar Hg concentrations with the life period of samples.…”
Section: Variation Of Foliar Hg Concentrations With Foliar Life Periodsupporting
confidence: 80%
“…We therefore suggest that differences in daily foliar Hg uptake rates between the sampling years 2015 and 2017 are negligible. In agreement with previous studies (Ollerova et al, 2010;Hutnik et al, 2014;Navrátil et al, 2019;Wohlgemuth et al, 2020;Pleijel et al, 2021), we found a clear trend of Hg concentrations in differently aged needles with older needles exhibiting higher Hg concentrations (Fig. 7), demonstrating that Hg accumulation continues in older needles.…”
Section: Foliar Hg Uptake and Geographic And Tree-specific Parameterssupporting
confidence: 93%
“…Ash leaves exhibited highest Hg concentrations (32.2 ± 5.7 ng Hg g -1 d.w.; n = 10), followed by beech leaves (25. Increasing foliar Hg concentrations with progressing sampling date are in line with previous observations demonstrating that at individual sites Hg concentrations increased linearly over the growing season (Rea et al, 2002;Laacouri et al, 2013;Wohlgemuth et al, 2020;Pleijel et al, 2021). To make Hg levels in foliage sampled at different times comparable, we calculated daily foliar Hg uptake rates by normalizing foliar Hg concentrations with the life period of samples.…”
Section: Variation Of Foliar Hg Concentrations With Foliar Life Periodsupporting
confidence: 76%
“…Hg in foliage originates predominantly from the air, and it can be delivered to the soil through the litter (Tomiyaso et al 2003). Adding to that, the atmospheric Hg uptake in foliage dominates over Hg release (Pleijel et al, 2021). Since normally the main source of Hg into the foliage is atmospheric and minimally through the soil, this explains the higher Hg concentration in the foliage, while in the stems the main uptake is from the soil and it seems to be minimal (Tomiyasu et al, 2005) explaining the much lower level of Hg concentration in the stems than that in the foliage.…”
Section: Hg Concentration In Plant Tissues Soil and Litter In The Stu...mentioning
confidence: 99%